The politics of language in Colombia and beyond - Lagnado, Jacob (Íkala, Revista de Lenguaje y Cultura, 1999)
The author presents a critical understanding of the dimensions of English teaching and learning in Colombia. The criteria for language teaching is market-based. His reflection leads him to consider their political. economical and cultural aspects; among them, the author states that Die needs of capital determine both the language taught and the way it Is taught.